Explanation:
To apply the distributive property, we need to multiply each term inside the parentheses by the coefficient outside.
2(a+5) = 2 * a + 2 * 5 = 2a + 10
4(2a+3) = 4 * 2a + 4 * 3 = 8a + 12
Therefore, the expression becomes:
2a + 10 + 8a + 12 - 10
Combining like terms, we can simplify further:
2a + 8a = 10a
10 + 12 - 10 = 12
Therefore, the simplified expression is:
10a + 12
Apply the Distributive Property and Combine like Terms to generate an expression equivalent to 2(a+5)+4(2a+3)−10
(1 point)
Responses
9a+12
9 A plus 12
10a+12
10 A plus 12
12a+10
12 A plus 10
10a+22
1 answer